Harnessing Clinical Trial Capacity to Mitigate Zoonotic Diseases: The Role of Expert Scientists in Ethiopia - Belay, Senait; Giday, Mirutse; Manyazewal, Tsegahun (Frontiers in Public Health, 2021)
Background: The emergence and resurgence of zoonotic diseases have continued to be a major threat to global health and the economy. Developing countries are particularly vulnerable due to agricultural expansions and domestication of animals with humans. Scientifically sound clinical trials are important to find better ways to prevent, diagnose, and treat zoonotic diseases, while there is a lack of evidence to inform the clinical trials' capacity and practice in countries highly affected with the diseases. This study aimed to investigate expert scientists' perceptions and experiences in conducting clinical trials toward zoonotic diseases in Ethiopia. Methods: This study employed a descriptive, qualitative study design. It included major academic and research institutions in Ethiopia that had active engagements in veterinary and public health researches. It included the National Veterinary Institute, the National Animal Health Diagnostic and Investigation Center, the College of Veterinary Medicine at Addis Ababa University, the Ethiopian Public Health Institute, the Armauer Hansen Research Institute, and the College of Health Sciences at Addis Ababa University. In-depth interviews were conducted with expert scientists. Data were collected from October 2019 to April 2020. Data analysis was undertaken using open code 4.03 for qualitative data analysis. Results: Five major themes, with 18 sub-themes, emerged from the in-depth interviews. These were: challenges in the prevention, control, and treatment of zoonotic diseases; One Health approach to mitigate zoonotic diseases; personal and institutional experiences in conducting clinical trials on zoonotic diseases; barriers in conducting clinical trials toward zoonotic diseases; and strategies that promote conducting clinical trials on zoonotic diseases. Conducting clinical trials on zoonotic diseases in Ethiopia is hampered by a lack of clearly articulated ethics and regulatory frameworks, trial experts, financial resources, and good governance. Conclusion: In Ethiopia, conducting clinical trials on zoonotic diseases deserves due attention. Strengthening institutional and human resources capacity is a pre-condition to harness effective implementation of clinical trials on zoonotic diseases in the country. In Ethiopia where skilled human resource is scarce, One Health approach has the potential to form multidisciplinary teams to systematically improve clinical trials capacity and outcomes in the country.